Sleep Quality of Students in the International Association of Students in Economics and Business (AIESEC), Padjadjaran University - Alif Aria Wardana (Mulawarman International Conference on Tropical Public Health, 2025)
College students who are actively involved in organizations often experience irregular sleep patterns due to heavy academic and extracurricular demands. Sleep deprivation has become a norm among students, despite its negative effects on physical health, emotional regulation, and cognitive performance. This study addresses the practical and scientific gap regarding the relationship between sleep quality and productivity among AIESEC members at Universitas Padjadjaran. The research aimed to assess students’ sleep quality and analyze whether it influences their organizational performance. A total of 100 AIESEC members (63 females and 37 males, aged 16–22) participated in this study. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI), while productivity was evaluated through the Personal Development Plan (PDP) scores. Data from both instruments were analyzed using descriptive statistics and regression analysis to determine correlations between PSQI and PDP results. Its found that 94% of respondents had poor sleep quality (PSQI > 5), averaging sleep duration of 5–6 hours per night. Despite this, most students achieved high performance levels, as 73% of them scored “Over Achieved” in their PDP assessments. Regression analysis indicated no significant correlation between sleep quality and productivity (R2 ≈ 0). These results suggest that while poor sleep quality is prevalent among AIESEC students, it does not directly hinder their short-term productivity. However, the findings emphasize the importance of promoting healthy sleep habits to prevent long-term health and cognitive consequences. Future studies should incorporate academic performance to further explore sleep’s broader impact.